Application of different heuristic classes in memory-based and stimulus-based decisions - Kwiatkowski, Lukasz (2015)
This paper studies the drivers of heuristic application in different decision types. The study compares differences in frequencies of heuristic classes' such as recognition, one-reason choice and trade-off applied in, respectively, memory-based and stimulus-based choices as well as in high and low involvement decisions. The study has been conducted online among 205 participants from 28 countries.